A high-performance Na-storage cathode enabled by layered P2-type KxMnO2 with enlarged interlayer spacing and fast diffusion channels for sodium-ion batteries. Issue 47 (9th November 2022) - Liu, Ningbo; Zhao, Xiaoying; Qin, Bin; Zhao, Dongdong; Dong, Huanhuan; Qiu, Mande; Wang, Liubin
Abstract : The K + -pre-intercalated Mn-based layered oxides with enlarged interlayer spacing ensure the expansion of diffusion channels enabling fast and stable Na + diffusion and show good electrochemical performance for SIBs. Abstract : Layered manganese-based oxides are considered the most promising candidates for cathode materials for sodium-ion batteries (SIBs) because of their high energy density, facile synthesis process, and abundant elemental resources. However, the relatively large size of Na + diffusing in the narrow layer spacing causes inevitable structural failure and sluggish diffusion kinetics during the insertion/extraction process resulting in poor cycling performance. Here, we designed and synthesized a P2-type K + -expanded manganese-based layered metal oxide (K0.69 MnO2, abbreviated as KMO), which possesses stabilized and enlarged Na + diffusion channels for high energy density SIBs. The distensible layered interlayer space of KMO (6.36 Å) compared to that of pristine P2-Na0.67 MnO2 (NMO, 5.62 Å) can provide larger ionic diffusion channels and more Na + storage sites, which enables fast Na + diffusion and ensures high rate performance. Consequently, the prepared KMO cathode delivers a high reversible capacity of 167.9 mA h g −1 (at 20 mA g −1 ), a fast rate capability of 112.5 mA h g −1 at 500 mA g −1, and good cycling stability with a capacity retention of 87.6% after 100 cycles at 50 mA g −1 . Furthermore, a full battery assembled with pre-activated KMO as the cathode and commercial hard carbon as the anode could deliver a high energy density of 195.4 W h kg −1 based on the total active mass of the cathode and anode. This investigation provides new insights into designing high-performance cathode materials with fast ion diffusion channels for SIBs and beyond.